Investigating the impact of gamification components on online learners’ engagement - Chen Meng; Mengyuan Zhao; Zilong Pan; Qianqian Pan; Curtis J. Bonk (Smart Learning Environments, 2024)
Abstract As online learning and teaching are becoming an educational trend, online students’ engagement will directly impact the learning and teaching effects and outcomes. A scientific application of gamification in online learning, teaching, and online course design will improve online learners’ learning experience and help build a better virtual learning context for online learners worldwide. This study focuses on how gamification can engage online students from skills, emotional, participation, and performance perspectives. The gamification components investigated in this study are Points (also called Anar Seeds in the context of this study) and Badges, the most widely used components in gamification design in education, and online instructors have primarily used them to motivate students’ learning and acknowledge their achievements by timely rewarding specific learning behavior or performance. A mixed method has been applied to explore further the relationships between gamification components and online students’ engagement and how online students perceive the impacts of gamification on their online learning experience. The findings show a significant correlation between Points and online students’ skills, emotional, participation, and performance engagement, while it exists only between Badges and online students’ participation engagement. The findings also reveal mixed perceptions of online students towards gamification. Study limitations regarding lack of age criterion, limited measurement indicators, and oversimplification of survey responses have also been discussed. It is suggested that future research can be conducted from either the instructors’ or the gamification designers’ perspectives to determine any other factors that might contribute to the implementation of gamification in the online learning context.